The sacred monstrous : a reflection on violence in human communities - Hamblet, Wendy C., 1949- (Lexington Books, 2004)
In The Sacred Monstrous author Wendy Hamblet traces the historical and social fact of violence through the work of Girard, Bloch, Lorenz and Burket. She takes up the charge advanced by social theorists, anthropologists and others that violence is steeped in our being; it pervades our generations and is imbedded in the ethos of our modern institutions. Hamblet's discussion of human history re-frames our understanding of how violence works in history and society. The Sacred Monstrous is a salient work of continentally informed philosophy that contributes significantly to any discussion of violen.